2019
DOI: 10.1136/bmjopen-2018-028768
|View full text |Cite
|
Sign up to set email alerts
|

Cohort profile: l’Actuel Pre-Exposure Prophylaxis (PrEP) Cohort study in Montreal, Canada

Abstract: PurposeThel’Actuel PrEP Cohortwas established to monitor the uptake, effectiveness, safety and changes in sexual risk behaviours among individuals receiving pre-exposure prophylaxis (PrEP) for the prevention of HIV. This prospective dynamic cohort is based at Clinique médicale l’Actuel, a large sexual health clinic located in Montreal, Canada.ParticipantsSince the cohort inception in January of 2013 through June 2018, 2156 individuals consulted for PrEP as participants in the l’Actuel PrEP Cohort. Median age w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 23 publications
4
36
1
Order By: Relevance
“…Among the seven individuals who stopped PrEP and subsequently developed HIV, factors impacting continued PrEP use included substance use, mental health and housing concerns; difficulty accessing PrEP due to cost, insurance and the need for medical and laboratory visits; difficulty weighing PrEP’s benefit versus one’s self‐perceived HIV risk; and entering a primary partnership. HIV incidence after stopping PrEP was similar to that in a Boston LGBT primary care clinic [11 but lower than that seen in a Los Angeles LGBT primary care clinic [10 and Montreal sexual health clinic [12] potentially due to our study being performed among a general primary care population. A strength of this analysis is that we were able to rigorously ascertain HIV diagnoses by leveraging the SFDPH/CDC’s enhanced HIV surveillance system.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Among the seven individuals who stopped PrEP and subsequently developed HIV, factors impacting continued PrEP use included substance use, mental health and housing concerns; difficulty accessing PrEP due to cost, insurance and the need for medical and laboratory visits; difficulty weighing PrEP’s benefit versus one’s self‐perceived HIV risk; and entering a primary partnership. HIV incidence after stopping PrEP was similar to that in a Boston LGBT primary care clinic [11 but lower than that seen in a Los Angeles LGBT primary care clinic [10 and Montreal sexual health clinic [12] potentially due to our study being performed among a general primary care population. A strength of this analysis is that we were able to rigorously ascertain HIV diagnoses by leveraging the SFDPH/CDC’s enhanced HIV surveillance system.…”
Section: Discussionsupporting
confidence: 51%
“…Despite many individuals stopping PrEP due to low self‐perception of risk, prior studies have also shown relatively large numbers of HIV infections after PrEP discontinuation [10‐12]. In a prior analysis, we found that African‐Americans, transgender women and younger participants were more likely to discontinue PrEP in our system, in spite of disproportionate HIV incidence in these groups [16].…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Currently, only daily use of PrEP is recommended in Canada. However, 'on demand' PrEP (intermittent PrEP, taken at the time of sexual activity) is more readily accepted and used in some jurisdictions (Greenwald et al, 2019;Molina et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, only daily use of PrEP is recommended in Canada. However, ‘on demand’ PrEP (intermittent PrEP, taken at the time of sexual activity) is more readily accepted and used in some jurisdictions (Greenwald et al., 2019; Molina et al., 2017). In the context of public health, patients often enter the BC PrEP program through a visit with a nurse in consult with, or directly through a licensed physician or nurse practitioner.…”
Section: Introductionmentioning
confidence: 99%